Hubungan peran teman sebaya dengan pemilihan jajanan pada siswa sekolah dasar - Novita Sari; Putri Zahara; Dian Devita; Lisnawati Rahayu; Azhar Mualim (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: The incidence of illness and food poisoning caused by street food among school-age children is currently on the rise. School-age children develop snacking habits that are difficult to break, and snacks that do not meet health and nutritional requirements can be detrimental to their health. Therefore, children's ability to choose healthy snacks is crucial. Purpose: To determine the relationship between the role of peers and the choice of snacks among students. Method: This study employed a quantitative analytical method with a cross-sectional approach. The population and sample were all 73 fifth and sixth grade students of SD Negeri 1 Teubeng, Pidie Regency. The study was conducted from October 26 to November 6, 2024. Results: The study showed that the majority of respondents chose healthy snacks, as many as 40 people (54.8%) and the majority had a positive peer role, as many as 42 people (57.5%). Statistical tests showed a relationship between the role of peers and snack choices among students, Pidie Regency, with a p value <0.05 (0.001). Conclusion: There is a significant relationship between the role of peers and snack choices among students. Keywords: Peer Role; Snacking Behavior; Students. Pendahuluan: Angka kejadian penyakit dan keracunan akibat makanan jajanan pada anak usia sekolah saat ini cenderung meningkat. Anak usia sekolah memiliki kebiasaan jajan yang sulit dihilangkan, sementara makanan jajanan yang tidak memenuhi syarat kesehatan dan gizi dapat mengancam kesehatan. Sehingga, kemampuan anak dalam memilih jajanan yang sehat sangat diperlukan. Tujuan: Untuk mengetahui hubungan peran teman sebaya dengan pemilihan jajanan. Metode: Penelitian ini menggunakan metode kuantitatif analitik dengan pendekatan cross sectional. Populasi sekaligus sampel dalam penelitian ini adalah seluruh siswa dan siswi kelas V dan VI SD Negeri 1 Teubeng Kabupaten Pidie yang berjumlah 73 orang. Penelitian dilaksanakan pada tanggal 26 Oktober sampai dengan 06 November 2024. Hasil: Mayoritas responden memilih jajanan sehat sebanyak 40 orang (54.8%) dan mayoritas memiliki peran teman sebaya yang positif sebanyak 42 orang (57.5%). Uji statistik menunjukkan adanya hubungan antara peran teman sebaya dengan pemilihan jajanan pada siswa dengan nilai p < 0.05 (0.001). Simpulan: Terdapat hubungan yang signifikan antara peran teman sebaya dengan pemilihan jajanan pada siswa Sekolah Dasar. Kata Kunci: Peran Teman Sebaya; Perilaku Jajanan; Siswa.